The Millennial Shopper : Rethinking Customer Experience in the Digital Age - Sleziaková, Zuzana; Lhotáková, Markéta, 1971-; Olšanová, Květa; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The objective of the presented master’s thesis is to investigate the shopping preferences of Czech millennial customers, who will soon represent the largest consumer segment in the marketplace. The theoretical part discusses different retail business models and their evolution over time, along with disruptive technologies, changing the traditional face of retail. To provide a theoretical basis for later analysis, this part also elaborates on the concept of customer shopping behavior and presents the model of channel choice. The practical part is built upon an empirical study, conducted as a two-stage research process consisting of in-depth interviews and a questionnaire. The final chapter summarizes the findings inferred about the studied sample of Czech millennials with regards to pre-determined hypotheses derived from secondary research. Additionally, practical implications for retailers and local businesses are addressed.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses